Evaluation of Mechanical Damages in SOFCs during Start/Stop Operation by Using Acoustic Emission Technique. (30th May 2017) - Kumada, Keigo; Sato, Kazuhisa; Hashida, Toshiyuki
Abstract : This paper presents an acoustic emission (AE) method for detecting the mechanical damage in anode-supported cells (ASCs). Start/stop cycle tests (between RT and 800°C) were carried out using single cells. After 2 cycle start/stop cycles, no damage was induced in the cells and their electrical performances were maintained without degradation. The experimental results indicated that the AE technique employed in this study allowed us to distinguish the damages in the cells from the cracking in the glass seals. In addition to this result, the mechanical damages during redox treatments were evaluated using the AE technique. The electrochemical evaluation performed concurrently with the redox treatments demonstrated the validity and significance of AE monitoring for detecting mechanical damages in SOFCs.